2008
DOI: 10.1093/pcp/pcn041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blue Light Deficiency on Acclimation of Light Energy Partitioning in PSII and CO2 Assimilation Capacity to High Irradiance in Spinach Leaves

Abstract: Blue light effects on the acclimation of energy partitioning characteristics in PSII and CO2 assimilation capacity in spinach to high growth irradiance were investigated. Plants were grown hydroponically in different light treatments that were a combination of two light qualities and two irradiances,i.e. white light and blue-deficient light at photosynthetic photon flux densities (PPFDs) of 100 and 500 micromol m(-2) s(-1). The CO2 assimilation rate, the quantum efficiency of PSII(PhiPSII) and thermal dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 41 publications
3
54
0
1
Order By: Relevance
“…For Cattleya orchids, production of multiple green protocorms was also highest in green light (Islam et al 1999). According to Matsuda et al (2008), a larger blue-light fraction, as provided by the BL lamps used in our experiments, is generally associated with the development of ''sun-type'' plants. Besides, Rajapske and Kelly (1993) showed that plants grown under green and blue lights had similar responses, probably because cryptochromes are green-light receptors (Folta and Maruhnich 2007).…”
Section: Discussionmentioning
confidence: 69%
“…For Cattleya orchids, production of multiple green protocorms was also highest in green light (Islam et al 1999). According to Matsuda et al (2008), a larger blue-light fraction, as provided by the BL lamps used in our experiments, is generally associated with the development of ''sun-type'' plants. Besides, Rajapske and Kelly (1993) showed that plants grown under green and blue lights had similar responses, probably because cryptochromes are green-light receptors (Folta and Maruhnich 2007).…”
Section: Discussionmentioning
confidence: 69%
“…Plants grown under blue light showed similar photosynthesis to those adapted to high light conditions (Matsuda et al, 2008). A relatively higher proportion of blue light can cause leaves to present so-called "sun type" characteristics and these leaves had high LMA and photosynthetic capacity (Matsuda et al, 2004;Matsuda et al, 2008;Hogewoning et al, 2010b). In this study, we found that the Pn of leaves grown under RB was higher than that of leaves grown under R and B, but had no significant difference compared with leaves grown under W (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies showed that the Pn of plants grown under red light was lower than that of plants grown under white fluorescent light or a mixture of red and blue light (Goins et al, 1997;Yorio et al, 2001;Matsuda et al, 2004). Plants grown under blue light showed similar photosynthesis to those adapted to high light conditions (Matsuda et al, 2008). A relatively higher proportion of blue light can cause leaves to present so-called "sun type" characteristics and these leaves had high LMA and photosynthetic capacity (Matsuda et al, 2004;Matsuda et al, 2008;Hogewoning et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…In some investigations into plants, it has been tried to avoid the spectra out of PAR region by using a proper light source radiating within PAR, 36,37 or using filters to prevent plants from UV, FR, or IR spectra. [38][39][40] In most reports neither of these two techniques have been employed nor have been mentioned if used, this is in spite of the fact that data taken under artificial light sources are potentially the most erroneous ones. …”
Section: -27mentioning
confidence: 99%